Exploring Mothers' Perspectives and Experiences on Stunting: Implications for Interventions at Health Center - Wulandari, Ririn; Putri, Savira Izzati; Bardie, Nafiza Iqbal (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Stunting is one of prevalent form of malnutrition affecting children worldwide. According to the World Health Organization (WHO), approximately 148.1 million children under the age of five are classified as stunted, meaning their height is below the expected standard for their age. It is suspected that stunting associated with developmental delays in children. Stunting can result from multiple factors, one of which is the lack of maternal knowledge and awareness regarding this condition. Purpose: This study aims to describe the experiences and understanding of mothers with children diagnosed with stunting. Methods: This research employs a qualitative descriptive design. The study sample consists of eight mothers with stunted children aged 1–5 years, selected using purposive sampling and snowball sampling. Data analysis was conducted using content analysis. Results: The findings indicate that most respondents perceive stunting merely as a condition characterized by short stature and low body weight, often attributing it to genetic factors. Their knowledge and understanding of children's dietary patterns and maternal nutrition during pregnancy remain incomplete. Additionally, environmental hygiene practices are limited to basic activities such as sweeping, mopping, and dusting, without considering other hygiene aspects that may impact child health. Conclusion: Although respondents regularly attend posyandu (integrated health service posts) and acknowledge its benefits, and receive information about stunting from multiple sources such as posyandu, midwives, and community health volunteers (kader kesehatan), the absence of a structured and routine stunting awareness program in the village poses a significant challenge in strengthening maternal understanding and prevention efforts. The information received is lacks depth, resulting in suboptimal application of knowledge in daily practices.